ответ: n=16
Объяснение:
a₁=−10,2;
a₂=−9,5;
d=a₂-a₁=−9,5+10,2=0,7
aₙ=a₁+d(n-1)=−10,2+0,7(n-1)=−10,2+0,7n-0,7=0,7n-10,9
0,7n-10,9>0
0,7n>10,9
n>109/7
n>15 4/7
Т.к. n- натуральное число,то первый положительный член арифметической прогрессии под номером 16.
a₁ = - 10,2
a₂ = - 9,5
a₂ = a₁ + d
d = a₂ - a₁ = - 9,5 - (- 10,2) = - 9,5 + 10,2 = 0,7
aₙ > 0
a₁ + d(n - 1) > 0
- 10,2 + 0,7(n - 1) > 0
- 10,2 + 0,7n - 0,7 > 0
- 10,9 +0,7n > 0
0,7n > 10,9
n > 15 4/7
ответ : n = 16
ответ: n=16
Объяснение:
a₁=−10,2;
a₂=−9,5;
d=a₂-a₁=−9,5+10,2=0,7
aₙ=a₁+d(n-1)=−10,2+0,7(n-1)=−10,2+0,7n-0,7=0,7n-10,9
0,7n-10,9>0
0,7n>10,9
n>109/7
n>15 4/7
Т.к. n- натуральное число,то первый положительный член арифметической прогрессии под номером 16.
a₁ = - 10,2
a₂ = - 9,5
a₂ = a₁ + d
d = a₂ - a₁ = - 9,5 - (- 10,2) = - 9,5 + 10,2 = 0,7
aₙ > 0
a₁ + d(n - 1) > 0
- 10,2 + 0,7(n - 1) > 0
- 10,2 + 0,7n - 0,7 > 0
- 10,9 +0,7n > 0
0,7n > 10,9
n > 15 4/7
ответ : n = 16